PERENCANAAN STRATEGIS DAN PENINGKATAN MUTU PENDIDIKAN DI SMP KRISTEN PENABUR GADING SERPONG - Poelihawati, Ieke; Pongtuluran, Aris (Manajemen Bisnis Kompetensi, 2008)
The aim of this study is to find out the implementation of strategic planning and the development of a quality of education at SMPK PENABUR Gading Serpong. This study was carried out at SMPK PENABUR Gading Serpong using the descriptive method. The data were collected through interviews, observation, document study, and questionaires. The result has not reached the maximum level as mentioned in the strategic planning theories. The academic quality is high enough because of the intensive participation of teachers, students, and parents.Keywords: strategic planning, quality, intensive participation